2019
DOI: 10.1063/1.5090765
|View full text |Cite
|
Sign up to set email alerts
|

Ions’ motion in water

Abstract: Over the decades, a great deal of attention has been focused on the solvation and transport properties of small rigid monatomic ions such as Na + , K + , Li + , Cl − , and Br − due to their importance in physical chemistry. Much less attention has been devoted to polyatomic ions although many polyatomic ions (such as nitrate, acetate, sulfate, and ammonium) are of great importance in biological and chemical processes. While the translational diffusion of smaller rigid ions shows the remarkable nonmonotonic dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 114 publications
0
38
0
Order By: Relevance
“…The monomers rotate relative to each other in opposite ways along the two limiting paths. Previous studies 30,31 reported rotation of the interfacial β strands relative to each other, as characterized by a pseudodihedral angle (here denoted Φ β ) defined by the C α atoms of Tyr B26 , Phe B24 , Tyr B 26 , and Phe B 24 , where the primes distinguish one monomer from the other. In addition to Φ β , we calculate the pseudodihedral angle (Φ α ) between the geometric centers of the backbone atoms of the residues that define the dimeric interfacial alpha helices: Ser B9 -Leu B11 , Leu B17 -Cys B19 , Leu B 17 -Cys B 19 , and Ser B 9 -Leu B 11 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The monomers rotate relative to each other in opposite ways along the two limiting paths. Previous studies 30,31 reported rotation of the interfacial β strands relative to each other, as characterized by a pseudodihedral angle (here denoted Φ β ) defined by the C α atoms of Tyr B26 , Phe B24 , Tyr B 26 , and Phe B 24 , where the primes distinguish one monomer from the other. In addition to Φ β , we calculate the pseudodihedral angle (Φ α ) between the geometric centers of the backbone atoms of the residues that define the dimeric interfacial alpha helices: Ser B9 -Leu B11 , Leu B17 -Cys B19 , Leu B 17 -Cys B 19 , and Ser B 9 -Leu B 11 .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, Figure 8 of ref. 31 indicates a path which begins with a slight increase in Φ β coupled to an increase in β from approximately 0.6 to 1.1 nm. This initial step is followed by a 30 • decrease in Φ β coupled to a return to a dimer-like β (near 0.6 nm) as the dissociation progresses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, rotational dynamics can be very important from the study of pharmacokinetics, although they are often neglected and attention is primarily paid on the translational dynamics. In the case of solutes dissolved in water, the rotational dynamics is strongly affected by their local environment and particularly the HB network around them 50 . Translational diffusion of these solutes is often coupled to their rotational dynamics which in turn are coupled to similar motions of the surrounding water molecules 50 .…”
Section: Resultsmentioning
confidence: 99%
“…In the case of solutes dissolved in water, the rotational dynamics is strongly affected by their local environment and particularly the HB network around them 50 . Translational diffusion of these solutes is often coupled to their rotational dynamics which in turn are coupled to similar motions of the surrounding water molecules 50 . The reorientational dynamics of the Favipiravir in the present study was also studied in terms of the Legendre reorientational time correlation functions for specific intramolecular vectors of the cation:…”
Section: Resultsmentioning
confidence: 99%